2023
DOI: 10.1021/acs.analchem.3c02066
|View full text |Cite
|
Sign up to set email alerts
|

A Carbonate-Involved Amplification Strategy for Cathodic Electrochemiluminescence of Luminol Triggered by the Catalase-like CoO Nanorods

Abstract: The lumiol-O2 electrochemiluminescence (ECL) system constantly emits bright light at positive potential. Notably, compared with the anodic ECL signal of the luminol-O2 system, the great virtues of cathodic ECL are that it is simple and causes minor damage to biological samples. Unfortunately, little emphasis has been paid to cathodic ECL, owing to the low reaction efficacy between luminol and reactive oxygen species. The state-of-the-art work mainly focuses on improving the catalytic activity of the oxygen red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Thus, MOF PCN 224 constructed by connecting Zr 6 -oxygen clusters with TCPP may serve as a promising option for developing a porphyrin-based ECL biosensor with cathodic emission. Luminol is a well-established organic ECL luminophore with remarkable luminous efficiency, which can emit an intensive signal during the anodic process. Nonetheless, immobilization of luminol onto the electrode for fabricating biosensors remains a challenging task since it is an aqueous soluble small-molecular compound. Fortunately, the presence of an active amino group on the aromatic ring of the luminol molecule facilitates its conjugation with other nonsoluble materials for developing biosensors.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, MOF PCN 224 constructed by connecting Zr 6 -oxygen clusters with TCPP may serve as a promising option for developing a porphyrin-based ECL biosensor with cathodic emission. Luminol is a well-established organic ECL luminophore with remarkable luminous efficiency, which can emit an intensive signal during the anodic process. Nonetheless, immobilization of luminol onto the electrode for fabricating biosensors remains a challenging task since it is an aqueous soluble small-molecular compound. Fortunately, the presence of an active amino group on the aromatic ring of the luminol molecule facilitates its conjugation with other nonsoluble materials for developing biosensors.…”
Section: Introductionmentioning
confidence: 99%
“…ECL molecular luminophors such as luminol, Ru­(bpy) 3 2+ , and their derivatives have been studied for a long time because of their merits in good stability and high ECL signals, but they are also suffering from poor biocompatibility and high cost. In recent years, nanomaterials (nanoclusters, quantum dots, inorganic and organic nanomaterials, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…However, in recent years, several authors reported the cathodic ECL emission in various conditions, 55,59,60 such as with catalytic nanomaterials, e.g. zinc oxide nanoparticle-modified Ni-foam, 61 carbonized polydopamine nanotubes, 62 catalase-like CoO nanorods, 63 acetylene black oxide, 64 two-dimensional NiM metal–organic framework (MOF, with M = Fe, Co, and Zn). 65 By adjusting iron single atom structures, the enhancement mechanism of luminol cathodic ECL was investigated and found to involve the production of massive reactive oxygen species for the generation of luminol radicals.…”
Section: Introductionmentioning
confidence: 99%